NEUTROPHIL-TO-LYMPHOCYTE RATIO, LYMPHOCYTE-TO-MONOCYTE RATIO AND PLATELET-TO-LYMPHOCYTE RATIO CORRELATES WITH HISTOPATHOLOGICAL GRADING OF ORAL SQUAMOUS CELL CARCINOMA - Mihnea Octavian Petrescu; Gabriel Sebastian Petrescu; Cristina Munteanu; Adrian Camen; Dumitru Rădulescu; Valeriu Șurlin (Romanian Dental Association for Education, 2020)
Inflammation may have a role in the development of tumors and the apparition of metastasis. The objective of this study was to investigate the correlation between three inflammatory markers: neutrophil to lymphocyte ratio (NLR), platelet to lymphocyte ratio (PLR) and lymphocyte to monocyte ratio (LMR) in peripheral blood of patients with oral squamous cell carcinoma (OSCC) and cancer histopathological differentiation. Methods: Medical records of 205 patients diagnosed with oral maxillofacial cancer between January 2017 and June 2019 were retrospectively analyzed. All patients were divided in groups according to the histopathological results. We investigated pretreatment neutrophil-to-lymphocyte ratio (NLR), lymphocyte-to-monocyte ratio (LMR) and platelet-to-lymphocyte ratio (PLR) and compared them between the groups. Results: From 205 patients, 51 had basal cell carcinoma (BCC), 7 had well differentiated (squamous cell carcinoma) SCC, 36 had good and moderately differentiated SCC, 67 had moderately differentiated SCC, 21 had moderate and poorly differentiated SCC and 23 had low differentiated SCC. The NLR, PLR and LMR for each group suggested an increasingly inflammatory response as the SCC differentiation was lower. Positive lymph node metastasis of the neck was found in 47% of all low differentiated squamous cell carcinoma (SCC) compared with only 1,9% in patients BCC, with higher inflammatory response in patients with positive neck. Conclusions: We observed that poorer histological differentiation in SCC was connected with higher inflammatory response in pretreatment NLR, PLR and LMR.